MARKER INDICATORS OF DEGENERATIVE-DYSTROPHIC PROCESSES OF THE SPINE, PELVIS AND HIP JOINTS OF DYSPLASTIC GENESIS - Z. V. Koshkareva; M. B. Negreeva (Acta Biomedica Scientifica, 2018)
Degenerative and dystrophic diseases of the spine, pelvis and hip joints are considered as a single pathogenetically conditioned process with an interdependent condition. The significance of the problem is determined by the high incidence of spinal and hip dysplasia, the syndrome of mutual burdening, the diversity and polymorphism of clinical manifestations, the growth of disability, the difficulties of diagnosis and treatment. Questions remain about the root cause of the occurrence of combined lesions, their mutual influence. The aim of the work was to identify the most common, diagnostic, pathognomonic signs of dysplastic syndrome. The patients were examined according to a single diagnostic algorithm, including clinical and neurological examination, plain radiograph of the pelvis; spondylography, MSCT, MRI of the lumbar and lumbosacral spine; study of the locomotion act of walking, anthropometric measurements; statistical methods. We analyzed the results of treatment of 39 patients (26 women and 13 men; mean age – 53 years) with dysplastic syndrome including degenerative-dystrophic changes in the spine, pelvis and hip joints. The most common diagnostic signs of combined degenerative-dystrophic diseases of the spine and pelvis have been established, among which pain syndrome, noted in varying degrees in all patients. The established diagnostic indices, supplementing existing knowledge of the problem studied, will allow to specify diagnostics and optimize the treatment of combined degenerative-dystrophic diseases of dysplastic genesis.